TOLERANCE OF MARANDU GRASS TO EXCESS IRON AND MANGANESE (REVISTA DE AGRICULTURA NEOTROPICAL, 2023)
In soaked soils there is an increase in the availability of iron and manganese. Thus, it becomes important to investigate the tolerance levels of plants to excess of these nutrients. The objective was to evaluate the tolerance of Urochloa brizantha cv. Marandu cultivated in nutrient solution with different levels of iron and manganese. The experimental design was completely randomized with seven treatments and four replications. The treatments consisted of a nutrient solution and consisted of: 1- adequate concentration of Fe (8.22 mM) and Mn (2.05 mM); 2– Fe, four times the adequate concentration; 3– Fe, eight times the adequate concentration; 4– Mn, four times the adequate concentration; 5– Mn, eight times the adequate concentration; 6– Fe and Mn, four times the appropriate concentration, and; 7– Fe and Mn, eight times the appropriate concentration. The variables evaluated were visual diagnosis (symptomatology), shoot height, root volume, Fe and Mn content in shoots and dry mass production. Grass plants were not tolerant to excess Fe and Mn. The excess of nutrients promoted less development of the root system, with a reduction in volume and dry mass, and the treatment with the highest dose of nutrients resulted in the lowest values. Grass plants were sensitive to the increase in nutrient concentrations, showing reductions in total dry mass production of 55% for treatment with the application of the highest concentration of nutrients in relation to the adequate dose of Fe and Mn.